IGF2BP1, a Conserved Regulator of RNA Turnover in Cancer - Glaß, Markus; Misiak, Danny; Bley, Nadine; Müller, Simon; Hagemann, Sven; Busch, Bianca; Rausch, Alexander; Hüttelmaier, Stefan (Frontiers in Molecular Biosciences, 2021)
The oncofetal IGF2 mRNA binding protein 1 (IGF2BP1) promotes tumor progression in a variety of solid tumors and its expression is associated with adverse prognosis. The main role proposed for IGF2BP1 in cancer cells is the stabilization of mRNAs encoding pro-oncogenic factors. Several IGF2BP1-RNA association studies, however, revealed a plethora of putative IGF2BP1-RNA targets. Thus, at present the main conserved target RNAs and pathways controlled by IGF2BP1 in cancer remain elusive. In this study, we present a set of genes and cancer hallmark pathways showing a conserved pattern of deregulation in dependence of IGF2BP1 expression in cancer cell lines. By the integrative analysis of these findings with publicly available cancer transcriptome and IGF2BP1-RNA association data, we compiled a set of prime candidate target mRNAs. These analyses confirm a pivotal role of IGF2BP1 in controlling cancer cell cycle progression and reveal novel cancer hallmark pathways influenced by IGF2BP1. For three novel target mRNAs identified by these studies, namely AURKA, HDLBP and YWHAZ, we confirm IGF2BP1 mRNA stabilization. In sum our findings confirm and expand previous findings on the pivotal role of IGF2BP1 in promoting oncogenic gene expression by stabilizing target mRNAs in a mainly 3'UTR, m6A-, miRNA-, and potentially AU-rich element dependent manner.